PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN INSTITUT TEKNOLOGI TELKOM PURWOKERTO - Aulia Gati Nirmalasari; Ary Ferdian (Departemen Manajemen, 2019)
This study aims to determine the effect of organizational culture on the performance of employees of the Telkom Institute of Technology in Purwokerto. The sample used in this study was all permanent employees of the Purwokerto Institute of Technology, using non probability sampling methods with saturated sampling techniques totaling 75 respondents. Statistical analysis uses simple linear regression analysis. The results of the analysis show that organizational culture has a significant positive effect on employee performance, meaning that the stronger the organizational culture in an organization will improve employee performance.